The Effect of the Film Thickness, Cooling Rate, and Solvent Evaporation on the Formation of L-Menthol Ring-Banded Spherulites - Tamás Kovács; Tamás Kovács; Márton Detrich; Ferenc Gazdag; Masaki Itatani; István Lagzi (Crystals)
Periodic pattern formation is a prominent phenomenon in chemical, physical, and geochemical systems. This phenomenon can arise from various processes, such as the reaction and mass transport of chemical species, solidification, or solvent evaporation. We investigated the formation of ring-banded spherulites of l-menthol using a thin liquid film in a Petri dish. We found that the film thickness and cooling rate strongly influence the generation of crystallization patterns. We performed two-dimensional numerical simulations using the Cahn–Hilliard model to support the experimentally observed trend on the dependence of the layer thickness on the periodicity of the generated macroscopic patterns. In a specific scenario, we observed the formation of rings consisting of needle-like crystals on the cover of the Petri dish. This phenomenon was due to the evaporation of the menthol and its subsequent crystallization. In addition to these findings, we created crystallization patterns by solvent evaporation (using tert-butyl alcohol, methyl alcohol, and acetone).